Relationship Between Regular Exercise and Quality of Life Among Middle-Aged and Older Adults in Japan - Dongshou Yu; Masako Shimura; Masashi Kawanishi (Behavioral Sciences, 2025)
This paper clarified the correlation among quality of life (QoL) indicators, exercise implementation level, and exercise habits in middle-aged and older adults under identical exercise intervention conditions. The survey items were anthropometric and physiologic measurements, physical strength measurements, and exercise habits. During the 3-month experimental period, a weekly “health exercise course” served as the primary intervention. For all participants, anthropometric and physiologic measurements, physical strength tests, questionnaire surveys, and other surveys were conducted before and after the experiment; then, the pre- and post-intervention effects were compared. After the exercise intervention, significant differences were observed among middle-aged and older adults in terms of various parameters, such as weight, fat rate, diastolic pressure, systolic pressure, sit-up, standing on one foot, lower limb extension force, activity of daily living (ADL), and subjective well-being (PGC). ADL and PGC changed significantly in the participants who engaged in exercise more than twice a week. However, the participants who engaged in exercise for less than twice a week showed no significant differences in any parameters except the life satisfaction (LSI) mean; the LSI increased in the “Less than twice a week” exercise group but decreased in the “More than twice a week” group. In terms of average walking time per session, the “More than 30 min” exercise group showed significant differences in ADL and PGC, whereas the “Less than 30 min” group showed significant differences only in the LSI. The influence of exercise on QoL indicators of middle-aged and older adults, under the same exercise intervention conditions, is related to their exercise habits. This study highlights the benefits of physical exercise in middle-aged and older adults, emphasizing the importance of regular and sustained exercise for this population. Furthermore, the study provides a scientific basis for improving QoL in middle-aged and older adults, thus, to some extent, addressing the concerns related to the growing population of older adults.